Health-care technology management: developing the innovation skills through implementing soft TQM among Lebanese hospitals - Aoun, Malak; Hasnan, Norlena (Taylor & Francis Group, 2017)
The objective of this research is to determine the influence of implementing soft total quality management (TQM) on the innovation skills (INS) of employees in Lebanese hospitals.A quantitative methodology was applied through conducting a cross-sectional survey among the employees and health-care professionals at 13 accredited hospitals in Lebanon.The respondents agreed that they were implementing the soft TQM principles and practicing the INS.However, the results showed that soft TQM influenced INS through people-based management (p <.05) but not through continuous improvement (p >.05).The major contribution of this research is centred on its empirical part since there is a lack of empirical studies in the field of health care in Lebanon. In addition, the shift from the hard side to the soft side of TQM contributes significantly to the academic literature as well as the methodological part especially in terms of using structural equation modelling analysis.This study was limited because of lack of participation especially from the public health sector in Lebanon.Thus, future studies are recommended to extend the research geographically and include more hospitals from both private and public sectors